PERANAN INDUSTRI SONGKET DALAM MENINGKATKAN PENDAPATAN RUMAH TANGGA PENGRAJIN DI NAGARI HALABAN KABUPATEN LIMA PULUH KOTA - Herlina Effendi; Osmet Osmet; Ifdal Ifdal (JISPO : Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
Development of rural areas is one of the targets in achieving national development. Industry is a way to accelerate rural development in an effort to improve the living standards of the community, one of them is through a local wisdom-based industry, the Halaban Songket industry. This industry is believed to have great potential for the economy in Nagari Halaban. The purpose of this study was to determine the characteristics of the Halaban Songket home industry and the pattern of relations between entrepreneurs and craftsmen in the Halaban Songket Home Industry, and the role of the Halaban Songket industry as an alternative source of household income. This research was conducted with quantitative methods, namely surveys supported by qualitative data. 35 respondents were chosen randomly by multistage sampling method. The results of this study indicate that the characteristics of the Halaban Songket industry as a handicraft industry carried out by almost 70 percent of women in Nagari Halaban with an average age of craftsmen is 37 years and the level of junior high school education. Craftsmen and entrepreneurs form patron-client patterns in work relations and social relations activities. As well as the Halaban Songket Industry contributed 55.34 percent to the income of songket craftsmen households.